ASSA13-01-2 Gender Difference of Bleeding in Acute Myocardial Infarction Patients Aged 80 and Over. (29th April 2013) - Jing-guang, Luo; Ming, Yang; Ling, Han; Li-wei, Chen; Kang, Gao; Hai-feng, Liang; Ping, Chen
Abstract : Objective: To investigate the gender difference of bleeding in acute myocardial infarction patients aged 80 and over. Methods: Life-threatening bleeding and major or minor bleeding is defined according to TIMI criteria. In a cohort of AMI patients aged ≥ 80 years from 2003 to 2012 at CCU department in fuxing hospital, the bleeding condition and the gender difference of bleeding was evaluated. Results: 386 patients presenting with ST segment elevation AMI (STEMI) and non-STEMI were enrolled, which included 189 male and 197 female. Bleeding was observed in 37.6% of male and in 43.1% of female, Pearson chi-square showed that there was no gender difference in bleeding during hospitalisation, X 2 = 1.248, P = 0.264. In the male patients, 2.8% of TIMI life-threatening bleeding, 19.7% of major and 77.5% of minor bleeding were discovered. 4.7% of TIMI life-threatening bleeding, 7.1% of major bleeding and 88.2% of minor bleeding were observed in the female patients. There was no significant gender difference in TIMI bleeding, X 2 = 5.802, P = 0.057. Conclusions: Our study demonstrates that no significant gender difference in TIMI bleeding in oldest-old patients with AMI is discovered.